Rectal Invasion by Prostatic Adenocarcinoma That Was Initially Diagnosed in a Rectal Polyp on Colonoscopy - Ghilsuk Yoon (Journal of Pathology and Translational Medicine, 2019)
Despite anatomical proximity, prostatic adenocarcinoma with rectal invasion is extremely rare. We present a case of rectal invasion by prostatic adenocarcinoma that was initially diagnosed from a rectal polyp biopsied on colonoscopy in a 69-year-old Korean man. He presented with dull anal pain and voiding discomfort for several days. Computed tomography revealed either prostatic adenocarcinoma with rectal invasion or rectal adenocarcinoma with prostatic invasion. His tumor marker profile showed normal prostate specific antigen (PSA) level and significantly elevated carcinoembryonic antigen level. Colonoscopy was performed, and a specimen was obtained from a round, 1.5 cm, sessile polyp that was 1.5 cm above the anal verge. Microscopically, glandular tumor structures infiltrated into the rectal mucosa and submucosa. Immunohistochemically, the tumor cells showed alpha-methylacyl-CoA-racemase positivity, PSA positivity, and caudal-related homeobox 2 negativity. The final diagnosis of the rectal polyp was consistent with prostatic adenocarcinoma. Here, we present a rare case that could have been misdiagnosed as rectal adenocarcinoma.